Financial intermediation and the funding of biomedical innovation: A review - Lo, Andrew W.; Thakor, Richard T. (Journal of Financial Intermediation, 2023)
We review the literature on financial intermediation in the process by which new medical therapeutics are financed, developed, and delivered. We discuss the contributing factors that lead to a key finding in the literature—underinvestment in biomedical R&D—and focus on the role that banks and other intermediaries can play in financing biomedical R&D and potentially closing this funding gap. We conclude with a discussion of the role of financial intermediation in the delivery of healthcare to patients.